Developing a Model of Psychological and Social Consequences of Covid19 pandemic anxiety with the Mediating Role of Sense of Cohesion - Kamran Shivandi Chalicheh (مطالعات روانشناسی تربیتی)
The aim of this study was to "designing and developing a model of psychological and social consequences of Covid19 anxiety pandemic and to identify mediating role of sense of cohesion in nurses of Tehran hospitals”.This research in terms of purpose was applied and in terms of nature and method of data collection was descriptive-correlative research based on structural equation. The statistical population of this study included nurses working in coronavirus department of Tehran hospitals in 2021. The statistical sample was 384 cases that selected based on cluster sampling method. The research tools included Kessler's psychological distress questionnaire (2002), Pierce et al.'s (1991) interpersonal relationship, Antonovsky al.'s (1987) self-cohesion and dortaj al.'s (2021) coronavirus anxiety. Descriptive indicators and structural equation were used to data analysis.Findings showed that sense of cohesion had a mediating role in the causal relationship between coronavirus pandemic anxiety and psychological distress and interpersonal relations of nurses.Based on these findings, it can be concluded that focusing on interventions based on improving the sense of cohesion can be an appropriate tool to alleviate anxiety caused by the spread of coronavirus pandemic among nurses and psychologists and governors must pay attention to this important practical factor.